Penerapan Economic Value Added untuk Memaksimalkan Nilai Perusahaan: Studi Kasus PT XYZ - Prabowo, Hartiwi (Bina Nusantara University, 2004)
EVA is an indicator about the value creation from an investation. Positive EVA indicate that a company is sucess in creating added value for share holders. That sincronize with the purpose to maximize the company value. Applying EVA concepts on company will encourage the management to find out the true cost of capital of the company so the level of clean return from capital will be shown clearly.